2019
DOI: 10.21839/jaar.2019.v4i1.260
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Decolorization of Remazol Brilliant Blue Royal (RB 19) textile dye by White Rot Fungi

Abstract: Synthetic dyes are widely used by different industries with over 7 ×10 5 metric tons produced globally each year. Dyes pose adverse effects including chemical oxygen demand, visual pollution, cytotoxicity, genotoxicity, mutagenicity and carcinogenicity on various types of living organisms. The versatile white rot fungi (basidiomycetes fungi) have developed specialized ligninolytic enzymes for reductive cleavage of dyes and xenobiotics. The present study optimized the decolorization of Remazol brilliant blue ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This study revealed that the fungal strains SN40b and SN8c have RBB dye decolorization capabilities of up to 95% after five days of treatment. In this regard, Afiya, et al [ 39 ] reported the decolorization capabilities of Pleurotus ostreatus and Coriolus versicolor of up to 70% and 80%, respectively, against RBB dye in eight days of treatment. The strains evaluated in this study showed better results than the previously reported fungal isolates.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the fungal strains SN40b and SN8c have RBB dye decolorization capabilities of up to 95% after five days of treatment. In this regard, Afiya, et al [ 39 ] reported the decolorization capabilities of Pleurotus ostreatus and Coriolus versicolor of up to 70% and 80%, respectively, against RBB dye in eight days of treatment. The strains evaluated in this study showed better results than the previously reported fungal isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments carried out in a low nitrogen medium with a series fungi and mushrooms secreting different enzymes showed their capability to degrade such molecules. The list includes the following fungi: Sordaria fimicola (catalase, laccase, superoxide dismutase), Halosarpheia ratnagiriensis ( Pleurotus ostreatus ), and Flavodon flavus (oxidative (laccase, manganese peroxidase, and lignin peroxidase) the former two belonging to the Ascomycota and the third to the Basidiomycotas isolated from mangrove sediment (glucose oxidase and glyoxal oxidase) ( S. fimicola ), Coriolus versicolor (manganese peroxidase and laccase), and hydrolytic enzymes (cellulases, xylanases and tanases)), Ganodermalucidum (cellulase and hemicellulase lignocellulolytic enzymes), Agaricus brasiliensis (manganese peroxidase).…”
Section: From Fundamentals To Practical Improvements In Catalytic Pro...mentioning
confidence: 99%
“…The cell immobilization technique captures cells by attachment to the matrix through chemical binding and self-adhesion or physical entrapment in the gaps of fibrous or porous materials [43]. The immobilization technique has several advantages: ease of application, can be reused and regenerated, lower production costs, increased degradation efficiency, and increased resistance to environmental exchange like pH and temperature [48,49]. Another advantage of cell immobilization is that it can reduce protease activity and the risk of contamination [46].…”
Section: Fungal Cell Immobilization Technique -Based Decolorizationmentioning
confidence: 99%
“…Research results from Arikan et al [49] noted that Penicillium glabrum Pg1 (PG) mobilized in macroporous polymeric support (MPPS) was able to degrade textile waste by 98.2% and remove COD by 69.8% within three days at pH 5.5. PG immobilized in MPPS can be used for textile waste treatment without dilution and additional nutrient sources.…”
Section: Fungal Cell Immobilization Technique -Based Decolorizationmentioning
confidence: 99%
See 1 more Smart Citation